Crayfish can distinguish between natural and chemical stimuli as assessed by cardiac and locomotor reactions - Kuklina, Iryna; Ložek, Filip; Císař, Petr; Kouba, Antonín; Kozák, Pavel (Environmental science and pollution research international, 2018)
In this study, cardiac and locomotor activities of signal crayfish Pacifastacus leniusculus were investigated under exposure to a range of natural (i.e., odors of conspecific crayfish, predatory fish, food, and injured conspecific) and one chemical (i.e., disinfectant chloramine-T) stimuli. Crayfish locomotion was simultaneously initiated with an increase in heart rate only when affected by chloramine-T, while locomotor response was delayed in all cases (or was not manifested at all by some specimens) when disturbed by the natural stressors. The heart rate differences measured before and during the stimulation were arranged as follows: odor of conspecific crayfish (9.2 ± 7.1%) < predator (18.4 ± 13%) < food (33.5 ± 15.7%) < chloramine-T (41.1 ± 14.7%) < injured conspecific (51.8 ± 28.4%). Analysis of the peculiarities of crayfish heartbeat under exposure to the tested stimuli revealed complex cardiac responses as was previously observed by an electrocardiography approach, that is, a slowed heart rate followed by a delayed increase. Evaluation of the intrinsic parameters of crayfish bioindicators remains essential due to the possibility of detection of the substantial ethological responses even in motionless animals. The role and appropriateness of signal crayfish as a bioindicator of water quality is discussed; they seem to be an applicable species for this task due to their sufficient sensitivity and broad availability. In addition to providing a better understanding of stereotypic crayfish behaviors induced by common and chemical stressors, the results of this study may serve as reference data for the evaluation of crayfish suitability for water quality tests.
Keywords: tosylové sloučeniny; potrava z moře (živočišná); chloraminy; dezinficiencia; Disinfectants; Pacifastacus leniusculus; Heart Rate; Chloramines; srdeční frekvence; kvalita vody; Water Quality; Biomonitoring; Astacoidea; Seafood; zvířata; Invasive crayfish species (ICS); severní raci; Movement; Tosyl Compounds; Heart rate; Bioindicator; odoranty; Odorants; Animals